Collagen–curcumin nanocomposites showing an enhanced neuroprotective effect against short term focal cerebral ischemia. Issue 4 (10th January 2020) - Rathore, Pankaj; Arora, Indu; Rastogi, Shweta; Akhtar, Mohd.; Singh, Shruti; Samim, Mohammed
Abstract : A synthetic collagen–curcumin nanocomposite enhanced drug efficacy by increasing its bioavailability and showing slow and sustained drug release in the treatment against focal cerebral ischemia. Abstract : The effectiveness of curcumin in treating cerebral ischemia has been reported in recent studies. However, its mode of action is still not defined. The objective of the present study is to formulate collagen–curcumin nanocomposites which will work effectively against cerebral ischemia/reperfusion injury. Ischemic injury is followed by inflammatory damage and oxidative stress, which together contribute a lot in the pathogenesis of cerebral ischemia and may be considered a good target for treatment. The present study focused on examining the effectiveness of collagen–curcumin nanocomposites stabilized by increasing the degree of crosslinking in reducing oxidative stress associated with brain injury resulting from cerebral ischemia. The collagen nanoparticles were prepared by conjugating collagen on the surface of Tween©80 micelles, and further stabilizing them using crosslinkers. The effectiveness of the prepared nanocomposite was validated by performing infarct analysis followed by biochemical, behavioral, histopathological and immunohistochemical studies. The outcomes of this study are promising for the use of collagen–curcumin nanocomposites in showing neuroprotective potential in treating ischemic injury.